HPAM–HABS induced synthesis of a labyrinth-like surface of calcite via rhombohedral lattice growth from the nanoscale. Issue 25 (8th June 2018) - Ma, Zaiqiang; Mu, Yuqiang; Shi, Weiguang; Wang, Jun; Liu, Xiaoyang; Wang, Xiaofeng; Dong, Zhaohui
Abstract : A labyrinth-like structure is generated during the phase transformations from nano- to micron-sized via a terrace-ledge-kink growth model of a rhombohedral crystal. Abstract : Calcite crystals with labyrinth-like surfaces are synthesized in the HPAM–HABS system via a hydrothermal method. Calcite grows in an oriented direction, and nano-amorphous CaCO3 acts as a growth unit on the steps and kink sites. With the synergistic effect of HPAM and HABS, the labyrinth-like structure is generated during the phase transformation from nano- to micron-sized via terrace-ledge-kink growth of the rhombohedral lattice.